Faktor-Faktor Kepuasan Pelanggan Starbucks: Kualitas Pelayanan, Persepsi Harga, Promosi dan Kepercayaan Pelanggan - Muhani Muhani; Tiara Ayu Nurani (Fakultas Ekonomi dan Bisnis Universitas Nasional, 2022)
Purpose This study aims to analyze and test the effect or absence of the effect of service quality, price perception, promotion and customer trust in customer satisfaction in Starbucks Coffee customers in the Jakarta area. Methodology The analysis and testing method used is multiple linear regression analysis. With the formula Hair et al, the number of samples in the study consisted of 110 respondents. Findings The results stated that the quality of service and promotion had no effect on Starbucks Coffee customer satisfaction. Meanwhile, price perception and customer confidence have a positive and significant effect on Starbucks Coffee customer satisfaction. Suggestion For further researchers it is recommended that they be able to use different variables and products in their research and for starbucks coffee companies it is advisable to implement competition-based pricing strategies in an effort to improve price perception and can strive for solutions to customer suggestions and complaints to improve customer confidence